TSPO Radioligands for Neuroinflammation: An Overview - Silvia Salerno; Monica Viviano; Emma Baglini; Valeria Poggetti; Doralice Giorgini; Jacopo Castagnoli; Elisabetta Barresi; Sabrina Castellano; Federico Da Settimo; Sabrina Taliani (Molecules, 2024)
The translocator protein (TSPO) is predominately localized on the outer mitochondrial membrane in steroidogenic cells. In the brain, TSPO expression, low under normal conditions, results upregulated in response to glial cell activation, that occurs in neuroinflammation. As a consequence, TSPO has been extensively studied as a biomarker of such conditions by means of TSPO-targeted radiotracers. Although [11C]-PK11195, the prototypical TSPO radioligand, is still widely used for in vivo studies, it is endowed with severe limitations, mainly low sensitivity and poor amenability to quantification. Consequently, several efforts have been focused on the design of new radiotracers for the in vivo imaging of TSPO. The present review will provide an outlook on the latest advances in TSPO radioligands for neuroinflammation imaging. The final goal is to pave the way for (radio)chemists in the future design and development of novel effective and sensitive radiopharmaceuticals targeting TSPO.